Alcohol Abuse as a Militating Factor against Quality of Life for Migrants’ Youth Population in Selected Provinces of South Africa - Matlakala, F.K.; Makhubele, J.C.; Masilo, D.T.; Kwakwa, M.M.; Baloyi, T.V.; Mabasa, A.; Rabotata, N.E.; Mafa, P. (International Journal of Criminology and Sociology, 2021)
Migrants’ youth are seen as one of the vulnerable populations in South Africa. This is largely due to the fact that they are seen as people who come to take job opportunities of the youth in the host country. In order to cope with their fear and stress, migrants indulge in binge consumption of alcohol. It is in light of that that in this paper researchers aimed to accentuate alcohol abuse as a militating factor against the quality of life for migrants’ youth population in selected provinces of South Africa. The study adopted qualitative approach and case study design to highlight how alcohol is seen as a militating factor against quality of life. The study population was drawn from three provinces in South Africa using convenient sampling technique to sample three participants. Moreover, the data was collected telephonically in three selected provinces and analysed thematically. The findings indicate that due to the accessibility, availability, affordability and stress migrants’ youth indulge in binge consumption. Thus, researchers recommend that policymakers should make guidelines that will restrict mushrooming of alcohol outlets – be regulation to prohibit overcrowding of outlets in selected provinces of South Africa.